Mary Wollstonecraft Shelley's Frankenstein, or the Modern Prometheus: A Psychological Study of Unrepaired Shame - Severino, Sally K. (Journal of pastoral care & counseling, 2013)
Mary Wollstonecraft Shelley's modern Prometheus shows us the eternal punishment of unrepaired shame—eternal entrapment within the shame triangle of victim, perpetrator and rescuer. This paper describes how Shelley's insight—that lack of love creates a monster living in shame—is being confirmed by neuroscience and how this is exemplified in two characters—the creature and Victor Frankenstein. Additionally, it delineates how pastoral counselors can help those suffering from unrepaired shame